Sociopreneurship and Human Resource Management Strategies for Sustainable Social and Environmental Impact: Bibliometric Analysis - Teuku Muhammad Syauqi; Sharfina Sharfina (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This research conducts a comprehensive bibliometric analysis of literature on sociopreneurship, human resource management (HRM), and disruptive technology. The main focus of this research is to identify theme clustering patterns, current research trends, future research opportunities, and collaboration among researchers in this domain. Data was obtained from reputable academic databases such as Scopus, ScienceDirect, and  WOS, and then analyzed using VOSviewer software to map relationships between keywords, publications, and authors. The analysis results indicate a significant evolution in sociopreneurship research, with increasing attention on topics such as local economic empowerment, women's inclusion in social entrepreneurship activities, technological innovations for sustainability, and value-based organizational transformation. Literature with the highest citations emphasizes the importance of integrating sustainable HRM strategies with sociopreneurship practices, particularly in the development of social business models, education, and community skill enhancement. However, there are still research gaps, particularly regarding the application of sociopreneurship in specific sectors such as health and measurable social business models. These findings provide a conceptual and practical foundation for further research and encourage interdisciplinary collaboration in supporting inclusive and sustainable social and environmental impact.